1996
DOI: 10.1111/j.2042-7158.1996.tb03930.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunopharmacological Activity of the Purified Insoluble Glucan, Zymocel, in Mice

Abstract: Although it has been established that soluble glucan in fungi is important to host defence against infection, the importance of insoluble glucans is not clear. We have examined the in-vivo immunopharmacological activity of the insoluble glucan, zymocel. Administration of zymocel increased peritoneal exudate cell number and spleen weight, and enhanced: phagocytic activity, hydrogen peroxide production, and nitric oxide production of peritoneal exudate cells; the extravascular release of Evans blue (which might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…15,18 There is evidence of nitric oxide (NO) deficiency at the wound site in diabetic rats, and wounds heal more readily with NO supplementation, which indicates a crucial role for NO in wound repair. 35 Administration of b-glucans increases the NO production of cells in the peritoneal exudate, 17 and macrophages secrete NO, 11 a mechanism that also could have contributed to the wound healing effect in our model. Also glucan has been shown to scavenge free radicals, which could have improved wound healing.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…15,18 There is evidence of nitric oxide (NO) deficiency at the wound site in diabetic rats, and wounds heal more readily with NO supplementation, which indicates a crucial role for NO in wound repair. 35 Administration of b-glucans increases the NO production of cells in the peritoneal exudate, 17 and macrophages secrete NO, 11 a mechanism that also could have contributed to the wound healing effect in our model. Also glucan has been shown to scavenge free radicals, which could have improved wound healing.…”
Section: Discussionmentioning
confidence: 78%
“…11 b-Glucans stimulate cells from the monocyte-macrophage system in animals and humans. [12][13][14][15][16] They also exert antitumor activity in vitro and in vivo, 13,17,18 and protect against life-threatening infections, 12,16,19 qualities possibly caused by induction of cytokine expression from the monocyte-macrophage system. 14,18,20 The present study was undertaken to see if topical applications of the macrophage-stimulant, aminated b-1,3-Dglucan (AG), could improve wound healing in an animal model with diabetes mellitus (db/db mice).…”
mentioning
confidence: 99%
“…The tumor necrosis factor alpha (TNF-) level was measured with enzyme-linked immunosolvent assay (ELISA) according to the report of Suzuki et al 18) In the assay, monoclonal rat antimouse TNF-primary antibody (BD Biosciences, San Jose, CA) and polyclonal rabbit antirat TNF-antibody (Pierce Biotechnology, Rockford, IL) were used to detect rat TNFforms. Recombinant mouse TNF-(R&D Systems, Minneapolis, MN) was used as the standard.…”
Section: )mentioning
confidence: 99%
“…When target genes are turned on by NF-B, mRNA synthesis occurs, and protein expression will follow. Although it has been reported that 133-␤-glucan is able to activate NF-B (23) and induce TNF-␣ production (24,25), details of the relationship between NF-B and TNF-␣ transcription in response to 133-␤-glucan remain to be investigated. This study was designed to explore the details of the mechanisms regulating TNF-␣ expression induced by zymosan A at both the cellular and molecular levels.…”
mentioning
confidence: 99%